(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Today environmental issue has become an intimate and worrying matter of concern at all over the world. The concept of environment encompasses varied and all inclusive aspects of life because every creature has equal right to live and retain its existence on this earth. Main factors such as land, water, plants and air are rapidly eroding which adversely causes environmental imbalance.[1]Water pollution, air pollution, sound pollution, erosion of fertile land and excessive wastage of food products is increasing on large scale. Moreover, in every one or the other country traumas of earthquakes, tsunami, flood, draughts are being experienced which ultimately generates adverse living conditions for all creatures on earth.[2]